Main benefits of humanized birth and nursing performance - Oliveira, Ana Clara Fernandes de (2023)
It is proposed to study the main benefits of humanized childbirth and the performance of nursing taking into account the need to improve nursing techniques and patient care. To discuss the humanization of childbirth from the perspective of the nurse and the safety of the parturient and the baby. This is a literature review carried out in the SciELO, LILASCS, Institutional Repository databases. With the use of literature published between the years 2017-2022, and also with the application of inclusion and exclusion criteria for the selection of articles. The humanizing process of childbirth allows the intervention of professional nurses to promote a more familiar and welcoming environment for the parturient, enabling the active participation of mothers, ensuring that they are trained in all stages of the childbirth process, reducing anxiety and increasing the security. It was concluded that nurses play a very important role in the delivery process. Among other capabilities, it maintains and guarantees good practices and non-drug methods for pain relief, in addition to guiding mothers throughout the process.